Editorial: time trends in colectomy rates for ulcerative colitis in England—mixed methods brings mixed messages?. Issue 5 (10th February 2021) - Bodger, Keith
Abstract : LINKED CONTENT This article is linked to Worley et al and Worley & Faiz papers. To view these articles, visit https://doi.org/10.1111/apt.16202 and https://doi.org/10.1111/apt.16256